Review of Tertiary Irrigation Canals in the Namu Ukur Utara Village Namu Sira-sira Sei Bingei, Langkat District - Vikri Novandi Akbar; Sumono Sumono; Ainun Rohanah (Universitas Sumatera Utara, 2014)
The distribution system of water on the field of Suka Maju villages is done through tertiary canal (a soil canal). This can resulted in waterloss through evapotranspiration, percolation and seepage so that conveyance efficiency of water become so little. Therefor it’s needed to study about the system further more. This research was aimed to study the tertiary irrigation canal in the Suka Maju village Sei Krio Sunggal, Deli Serdang district. The result showed that in the field conveyance efficiency (at the same distance) was 68,39% for canal 1 and 95,92% for canal 2. Additionally the sedimentation was also found in the canal, so that it was important to redesign the dimensions of the tertiary canal. Thus the sedimentation as well as the scoured could be reduce. The best tertiary canal dimensions for canal 1 was a combination of 0,02% slope, canal width (B) of 0,42 m and the depth of water (D) of 0,21 m, while for canal 2 a combination of 0,02% slope, canal width (B) of 0,51 m and the depth of water (D) of 0,26 m. Key Words: Tertiary Canal, Waterloss, Conveyance Efficiency, Design of Canal.